On the Existence of the Optimal Control for Stochastic Functional Differential Equations Subject to External Disturbances - Yasynskyy, V. K.; Yurchenko, I. V. (Cybernetics and systems analysis, 2024)
The authors discuss the comparison theorem for solutions of stochastic functional differential equations subject to external disturbances and its application to a stochastic control problem. Keywords: comparison theorem, stochastic control, stochastic functional differential equations.